Peran Guru Pai dalam Menanggulangi Degradasi Moral Peserta Didik - diah, Diah khoirunisah (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2024)
The moral degradation of the nation's children is decreasing day by day. The issue of fights between students and teachers, acts of violence, thuggery, liquor consumption, traffic ethics, criminality, which is getting more and more complicated. The emergence of these cases is not merely due to the failure of Islamic religious education in schools that emphasise the cognitive aspect, but how all of that can encourage and move Islamic religious education teachers to re-examine and find solutions through the development of Islamic religious education learning. This article aims to see how the role and strategy of Islamic education teachers in overcoming the moral degradation of students today. This research uses a qualitative approach with a case study method related to the moral degradation of students. The data collection technique uses the literature observation method. The results of this study indicate that the role of PAI teachers in overcoming the moral degradation of students with Empowerment, Exemplary, and Screening can be categorised as successful. Degradasi moral anak bangsa semakin hari semakin menurun. Isu perkelahian antar pelajar dengan guru, tindak kekerasan, premanisme, konsumsi minuman keras, etika lalu lintas, kriminalitas, yang semakin hari semakin menjadi dan rumit. Timbulnya kasus-kasus tersebut tidak sematamata karena kegagalan pendidikan agama Islam di sekolah yang lebih menekan aspek kognitif, tetapi bagaimana semua itu dapat mendorong serta menggerakkan guru pendidikan agama Islam untuk mencermati kembali dan mencari solusi lewat pengembangan pembelajaran pendidikan agama Islam. Artikel ini bertujuan untuk melihat bagaimana peran dan strategi guru PAI dalam menanggulangi degradasi moral peserta didik saat ini. Penelitian ini menggunakan pendekatan pendekatan kualitatif dengan metode studi kasus yang berkaitan dengan degradasi moral peserta didik. Teknik pengumpulan data menggunakan metode observasi kepustakaan. Hasil penelitian ini menunjukkan bahwa peran guru Pai dalam menanggulangi degradasi moral peserta didik dengan Pemberdayaan, Keteladanan, dan Screening dapat dikategorikan berhasil.